2002
DOI: 10.1038/ng1049
|View full text |Cite
|
Sign up to set email alerts
|

The core-binding factor β subunit is required for bone formation and hematopoietic maturation

Abstract: Core-binding factor beta (Cbfbeta) is the common non-DNA-binding subunit of the Cbf family of heterodimeric transcription factors. Mice deficient in Cbfbeta have a severe block in fetal liver hematopoiesis at the stage of hematopoietic stem cell (HSC) emergence. Here we show that by providing Cbfbeta function in endothelial cells and hematopoietic progenitors we can rescue fetal liver hematopoiesis in Cbfbeta-deficient embryos. The rescued mice die at birth, however, with severe defects in skeletal development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
122
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(128 citation statements)
references
References 29 publications
6
122
0
Order By: Relevance
“…FGF2 regulation of Runx2 phosphorylation (53,54) and dephosphorylation (19,55) is required for transcriptional activation. Although early reports suggested that osteoblast-specific forms of Runx2 do not heterodimerize with CBF-␤ (30), more recent data suggest that formation a multiprotein Runx2-CBF-␤ heterodimeric complex is important for osteoblast differentiation (56,57). Via its three N-terminal RRM domains, MINT binds to the GT-rich sequences in the OCFRE (21) and stably organizes this complex to further augment Runx2-dependent transcription.…”
Section: Discussionmentioning
confidence: 99%
“…FGF2 regulation of Runx2 phosphorylation (53,54) and dephosphorylation (19,55) is required for transcriptional activation. Although early reports suggested that osteoblast-specific forms of Runx2 do not heterodimerize with CBF-␤ (30), more recent data suggest that formation a multiprotein Runx2-CBF-␤ heterodimeric complex is important for osteoblast differentiation (56,57). Via its three N-terminal RRM domains, MINT binds to the GT-rich sequences in the OCFRE (21) and stably organizes this complex to further augment Runx2-dependent transcription.…”
Section: Discussionmentioning
confidence: 99%
“…YS primitive erythropoiesis is unaffected. Restoration of CBFb expression under the control of TIE2 regulatory regions (Miller et al, 2002) rescues the establishment of FL haematopoiesis, although with diminished formation or maintenance of the hierarchically more primitive multilineage progenitors (colony-forming unit-granulocyte, erythrocyte, macrophage, megakaryocyte (CFU-GEMM)). There has been no detailed characterisation of the HSC compartment.…”
Section: Group I: 'Early' Regulatorsmentioning
confidence: 99%
“…6 Interestingly, both C/EBPa and CBFB are required for normal myeloid development and mutations in either can give rise to leukemia. [88][89][90] The dynamic relationship between PU.1 and GATA-1 during both the leukemic state of MEL cells and also upon MEL differentiation can be described in the following putative steps: at myeloid genes such as C/EBPa, PU.1 binds directly to DNA but its transactivation is antagonized by GATA-1 binding directly to PU.1 molecules on DNA. Activation of exogenous PU.1 combined with stable levels of GATA-1 create an excess of available PU.1, which is not paired by available GATA-1, thus altering the stoichemistry between these two proteins resulting in PU.1-mediated gene activation associated with acquisition of active chromatin mark Acetyl H3K9 near the PU.1-binding sites (Figure 1, right panels).…”
Section: Gata-1 and Pu1 Levels Are Determinants Of Leukemogenesismentioning
confidence: 99%